Investigation of Column Temperature and Validation of an HPLC-PDA Method for Hydrogen Peroxide Analysis in Hair Cosmetics under Tropical Environments - Dinalia Dinalia; Husain Sosidi; Ahmad Ridhay; Hannan Hannan; Khairuddin Khairuddin; Pasjan Satrimafitrah; Syamsuddin Syamsuddin (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Hydrogen peroxide (H₂O₂) is widely used as an oxidizing agent in hair cosmetic products, requiring reliable and validated analytical methods to ensure product safety and regulatory compliance. This study investigated the effect of column temperature and validated a high-performance liquid chromatography–photodiode array (HPLC–PDA) method for H₂O₂ determination in hair cosmetic formulations using triphenylphosphine (TPP) derivatization under tropical laboratory conditions. The triphenylphosphine oxide (TPPO) derivative exhibited a stable maximum absorbance at 222 nm within the concentration range of 20–120 ppm, which was selected as the detection wavelength. System suitability was evaluated at ambient temperature, 35, 40, 45, and 50 °C. Column temperatures between 40 and 50 °C fulfilled all system suitability and validation criteria, demonstrating acceptable efficiency, peak symmetry, retention time stability, and reproducibility. Among these conditions, 40 °C was selected as the optimum column temperature based on overall analytical performance and practical considerations. Method validation showed excellent linearity (correlation coefficient r ≥ 0.995; residual variance Vxo ≤ 5%), acceptable precision (%RSD ≤ 2%), and adequate sensitivity, expressed as limits of detection (LOD) and limits of quantification (LOQ). Accuracy evaluation using matrix-spiked samples yielded recoveries within the AOAC acceptance range (90–107%). Overall, the validated HPLC–PDA method at 40 °C with detection at 222 nm is robust and suitable for routine determination of H₂O₂ in hair cosmetic products under tropical conditions.